OC-100 Lorec registry– interim analysis of operative technique and perineal wound healing outcomes after abdomino-perineal excision. (22nd June 2015) - Jones, H; Crane, S; Moran, B; Cunningham, C
Abstract : Introduction: The LOREC perineal wound healing registry was developed to record data on abdomino-perineal excision (APE) for rectal cancer in colorectal units across the UK between 2012 and 2014 to understand current practice in operative techniques and patient outcomes. Initial interim results are reported. Method: Surgeons wishing to participate received secure web-based access to the registry. Collected data included pre-operative staging, operative details, pathology, early outcome and follow-up at 12 months. Results: Overall 43 units entered a total of 259 patients undergoing APE. These included 168 extralevator APE (ELAPE) procedures (65%) and 91 non-ELAPEs, comprising 73 'standard' APE, 9 intersphincteric, 2 ischio-anal and 7 unspecified procedures. The ELAPE and non-ELAPE groups are compared. In the ELAPE group there were 120 males (71%) with a median age of 66 years (range 38–93). In the non-ELAPE group there were 64 males (70%) with a median age of 68 years (range 32–97). The perineal component was performed prone in 151 (90%) of the ELAPE group versus 13 (14%) of the non-ELAPE group. The coccyx was removed in 123 (73%) of the ELAPEs and 7 (8%) of the non-ELAPEs. In the ELAPE group primary skin closure for the perineal component was performed in 119 (71%) while in 34 (20%) a flap was used (13 VRAM, 9 local myocutaneous and 12 fascio-cutaneous flaps). In 15 cases (9%) the surgeons reported no closure. In 111 (66%) a mesh, generally biological, was used in perineal closure. Mesh was most commonly used where the closure was primary but 9 flap closures also used mesh. In the non-ELAPE group primary closure was more common, being used in 76 (84%) while in 5 (5%) a flap was used. In 10 cases (11%) the surgeons reported no closure. Mesh was used less frequently in non-ELAPEs, with only 30 (33%) using a mesh; the majority (57%) of these were non-biological. Primary healing was achieved in 29% of ELAPE patients, the majority of whom were closed primarily, compared to 9% in the non-ELAPE group. There was no difference in wound healing by 4 weeks and both groups had a small number of patients who took more than 3 months to heal completely. There was no significant difference in length of hospital stay for the two groups. There was one post-operative death in each group; a peritonitis of unknown cause in the ELAPE group and a GI bleed in the non-ELAPE group. Conclusion: The LOREC registry has been a success in providing a summary of current practice and will be valuable in informing the design of future trials assessing APE techniques and reconstruction. In this series, ELAPE is performed in the majority of patients and primary closure with mesh appears to offer effective skin closure compared to flap. Disclosure of interest: None Declared.